372PReal-world fusion landscape in advanced Chinese pancreatic cancer using next generation sequecing: A multicenter study. (24th November 2019) - Shen, Y; Fang, S; Cai, X; Fang, Y; Lin, R; Zhang, Y; Li, J; Liang, X; Wang, L; Lin, L; Zhang, L; Feng, H; et al.
Abstract: Background: The therapeutic targets of pancreatic cancer (PC) are fewer. Cell-free DNA (cfDNA) has been a research hotspot in molecular tumour profiling. In advanced PC patients, malignant abdominal dropsy provides a wealth of tumour cells that can be investigated. The aim of this study is to investigate fusion landscape in advanced PC. Methods: A multicenter study in China was initiated from Oct. 2016, and PC patients have been enrolled as of Apr. 2019. To determine the fusion frequency in PC, we analysed data from 536 clinical PC cases, each of which had results from next-generation sequencing (NGS)-based 808 genes panel assay, analogous to the index patient. Results: Of this entire cohort, 24 patients (4.48%) were identified with fusions, including ARID1A-PIGV (1), HSD3BP4-HSD3B1 (1), CDKN2A-MTAP (1), PDE10A-BRAF (1), ETV6-NTRK3 (1), NOTCH1-RABL6 (1), ERRFI1-SLC25A33 (1), BRCA1-PTGES3L (1), MYCN-LINC00299 (1), CREBBP-CDIP1 (1), LPAR5-CHD4 (1), PMS2-ETV1 (1), RPTOR-ASPSCR1 (1), CHD2-SLCO3A1 (1), IDH2-SEMA4B (1), BAIAP2-RPTOR (1), CHEK1-OSBP (1), LRP1-KRT81 (1), TBX3-ACSS3 (1), RAB11FIP1-GPR124 (1), AXIN1-SNX29 (1), PPP2R1A-ZNF415 (1), BCL2L14-ETV6 (1) and BMX-NHS (1). BRAF, NTRK and BRCA1 fusions were seen in 12.50% (3/24) advanced Chinese pancreatic cancer fusion landscape patients. These three patients were diagnosed with pancreatic duct adenocarcinoma. For treatments, the BRAF fusion patient chose vemurafenib, another two patients chose chemotherapy, and this case of BRAF fusion patient responding to vemurafenib was actively being sought thru our database. Conclusions: Advanced Chinese pancreatic cancer fusion landscape is rich, BRAF and NTRK fusions are rare but potentially druggable in TKIs. Detection of BRAF, NTRK, BRCA1, EGFR, ALK, ROS1, RET and ERBB2 fusions should be part of comprehensive profiling panels to determine TKIs and direct appropriate combination therapeutic strategies. Legal entity responsible for the study: Yiyu Shen. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.